The Use Of Games In Teaching Vocabulary In Young Learners - Fairuz Dewi Raihan (Prosiding University Research Colloquium, 2021)
The purpose of this paper is to discuss the possibilities of improving the English vocabularymastery for young learners through the use of games. Several approaches and methodscan be used to teach English vocabulary to young learners. The method we use to collectinformation in making this journal is review articles, we use the journal as a reference.One good way to learn vocabulary is to use real objects that children can visualize later.They need to pay attention to learning to use words and repeating them too. The othermethod is the direct method where there is no translation and the use of the mother tongueis prohibited. The games used by the teacher to teach words to young learners are hotpotato game, memory challenge, last one standing, pictionary, bingo. From the applicationof the game, young learners can quickly and easily increase their English vocabulary.